2011
DOI: 10.1103/physreva.83.012707
|View full text |Cite
|
Sign up to set email alerts
|

Time evolution of electron transmission through a single glass macrocapillary: Charge build-up, sudden discharge, and recovery

Abstract: The time (i.e., integrated charge) dependence of electron transmission through a single glass macrocapillary was studied for incident 500-and 800-eV electrons at different capillary tilt angles. As the transmitted intensity goes to equilibrium, the centroid energies and corresponding energy values of the full width at half maximum of the transmitted electron distributions are found to vary in phase and out of phase with the transmitted intensity, respectively. Stable equilibrium was not fully reached even for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 20 publications
2
16
0
3
Order By: Relevance
“…This is typically observed for higher beam intensities as a sudden decrease in transmission, typically long after the guided beam fraction has saturated. In a study by Dassanayake et al [41] using electron beams, the sudden decrease in transmission was observed to be followed by a slow recovery, with the cycle eventually repeating. Several other studies of blocking have also been performed using nanocapillaries (see [42][43][44] and references therein).…”
Section: F Blocking Of Beam Transmissionmentioning
confidence: 97%
“…This is typically observed for higher beam intensities as a sudden decrease in transmission, typically long after the guided beam fraction has saturated. In a study by Dassanayake et al [41] using electron beams, the sudden decrease in transmission was observed to be followed by a slow recovery, with the cycle eventually repeating. Several other studies of blocking have also been performed using nanocapillaries (see [42][43][44] and references therein).…”
Section: F Blocking Of Beam Transmissionmentioning
confidence: 97%
“…In 2002 the discovery that charged particles can be guided through insulating capillaries [1] initiated numerous experimental and theoretical investigations of this phenomenon [2][3][4][5][6][7][8][9][10][11][12]. Guiding is of interest because the transmitted particles do not change their charge (in the case of ions) or lose significant portions of their kinetic energies (in the case of ions and lower energy electrons).…”
Section: Introductionmentioning
confidence: 99%
“…While a quiet period followed by an instant transmission phase was observed in the 90° and 180° samples, the data of the 360° helix capillary test show an intermediate phase in which the transmission was accompanied by strong noise. This is most likely the phase in which the transmission varies as a result of the dynamic evolution of additional negative charge patches, possibly accompanied with sudden discharges as reported by Dassanayake 17 . During the equilibrium the transmission efficiency was at around 74%, which is much lower compared to the previous samples.…”
Section: Discussionmentioning
confidence: 65%
“…2 ). We considered possible blocking effects that might have disturbed the guiding process due to overcharging as well as sudden discharges of a negative patch within the borosilicate glass capillary as observed in 2010 17 . The scenario of electron transmission after a quiet period has been observed in several studies 14 , 28 , where electrons were guided through PET nanocapillaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation